THE INFLUENCE OF CAREER EXPECTATIONS AND TECHNOLOGY LITERACY ON JOB-SEEKING INTENTION AMONG GENERATION Z THROUGH MOTIVATION: A CASE STUDY IN PEKANBARU - Salsabila Fasne; Hamsal Hamsal; Ezra Deavin Ulayya (Jurnal Apresiasi Ekonomi, 2026)
This study explores the influence of Career Expectations and Technology Literacy on Job-Seeking Intention (JSI) among Generation Z in Pekanbaru, with Motivation acting as a mediating variable. Through a quantitative approach, data was collected from 130 participants, including both students and recent graduates. The findings reveal that Career Expectations have an indirect influence on JSI through Motivation, emphasizing that while high Career Expectations shape Motivation, it is Motivation that more directly influences job-seeking behaviors. Additionally, Technology Literacy was found to significantly enhance JSI, highlighting the importance of digital skills in navigating modern job-search platforms. The study suggests that while Career Expectations set the foundation for motivation, it is the individual’s level of Motivation and Technology Literacy that drives their Job-Seeking Intensity. These results provide valuable insights into how Generation Z’s job-seeking behaviors are shaped by psychological and technological factors, offering practical implications for educational institutions and policymakers to better support the career readiness of young people. Keywords: Career Expectations, Technology Literacy, Job-Seeking Intention, Motivation, Generation Z, Pekanbaru